Effectiveness of a behavior change program on cardiometabolic risk factors in adult women (Research, Society and Development, 2022)
This study aimed to evaluate the effectiveness of a behavior change program, called Vida Ativa Melhorando a Saúde (Active Life Improving Health - VAMOS), on cardiometabolic risk factors in adult women. Study participants (> 18 years) were divided into two groups: intervention group (IG) and control group (CG). The GI participated in VAMOS, in 2016 and 2018, for three months, with 12 face-to-face meetings, once a week, for approximately 2 hours. The GC received general guidance on the importance of maintaining an active and healthy lifestyle before data collection. Both groups were evaluated at baseline and three months after the intervention. The evaluation consisted of a sociodemographic questionnaire, anthropometric measurements and blood collection to determine the biochemical profile. There was a reduction in uric acid (AU) (p